Implementasi Kerangka Kerja Cobit 4.1 Domain Acquire and Implement (AI) Terhadap Tata Kelola Teknologi Informasi (Studi Kasus: Dinas Komunikasi dan Informatika Kota Bukittinggi) - Fandy Adityo; Suprapto Suprapto; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Department of Communication and Information of Bukittinggi is one of the government institutions that have the authority to handle the government affairs on the field of communication and information. It facing some problems on governing and implementing their own assets. Hence, the IT governance evaluation was required using the COBIT 4.1 frameworks to all of the processes on Acquire and Implement (AI) domain. The purpose of this research was aimed to get know how is the existing condition of IT governance on Department of Communication and Information of Bukittinggi by assessing the maturity level and giving the recommendation in the form of the draft of the documents. The data was collected by doing several methods such as questionnaires, interviews, and observation. Respondents are defined by analyzing the RACI Chart. The result for the maturity level has an average of 1.57 and the gap analysis was 1.00. The target level was defined to be one level ahead of the existing conditions. To achieve that targets, the recommendation that given was by making Standard Operational Procedure (SOP) on all of the processes on Acquire and Implement (AI) domain and completing the documentation by doing it with a formal and standardized format. It will be later implemented on Department of Communication and Information of Buktttinggi so, the IT governance can be good and controlled.